Efficacy of PD-1 or PD-L1 inhibitors for the therapy of cervical cancer with varying PD-L1 expression levels: a single-arm meta-analysis - Yang, Jie; Yu, Haizan; Zhang, Yilei; Zhu, Mingli; Zhang, Mengyu; Wang, Qiming (Frontiers in Oncology, 2024)
Objective: To assess the effectiveness and tolerability of both PD-1 and PD-L1 inhibitors in advanced cervical cancer (CC), focusing on varying PD-L1 levels. Methods: A comprehensive exploration was carried out on EMBASE, PubMed, Cochrane Library databases as well as Web of Science up to May 25, 2024, for studies involving advanced CC patients receiving PD-1/PD-L1 inhibitors. Inclusion criteria were studies reporting objective response rate (ORR), disease control rate (DCR), median progression-free survival (PFS), as well as median overall survival (OS). Data extraction and quality assessment were performed by two reviewers using the JBI Case Series Critical Appraisal Checklist, followed by a meta-analysis via STATA/MP 16.0. Results: Five eligible studies comprising 223 patients were chosen. ORR and DCR were 42% (95% CI: 17%-66%, P = 0.00) and 70% (95% CI: 22%-117%, P = 0.00), respectively, in the PD-L1 positive patients and were 36% (95% CI: 17%-54%, P = 0.00) and 47% (95% CI: 30%-63%, P = 0.00), respectively, in patients with PD-L1 negativity. For patients exhibiting PD-L1 positivity, median PFS and median OS were 3.98 months (95% CI: 0.80-7.16, P = 0.01) and 11.26 months (95% CI: 3.01-12.58, P = 0.00), respectively. Conclusion: With PD-1/PD-L1 inhibitors, PD-L1 positive CC patients demonstrate superior ORR, DCR, median PFS, and median OS, underscoring PD-L1 as one biomarker for immunotherapy response.